Krisis Kebahagiaan di Tengah Perilaku Konsumtif Perspektif Al-Ghazali - Lailia, Khusnul; Novika, Aulia; Rosia, Rina; Waluyo, Agus (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research aims to examine the happiness crisis in modern society influenced by the dominance of materialism and consumerism, and to offer alternatives through the perspective of Imam Al-Ghazali's thought. In conventional economics, happiness is generally measured through utility and consumption satisfaction, but this approach has yet to comprehensively explain the spiritual and psychological dimensions of humans. This research uses a qualitative approach with a library research method through the study of Al-Ghazali's main works, particularly Ihya’ Ulumuddin, as well as various contemporary literatures on consumerism, happiness, and well-being psychology. Data were analysed using the content analysis method to systematically identify, categorise, and interpret the main concepts. The research results show that material-based happiness is illusory and temporary, and is correlated with increased anxiety and life dissatisfaction. The novelty of this research lies in the effort to reconstruct Al-Ghazali's concept of qana’ah not only as a spiritual value but also as an ethical and psychological mechanism in responding to modern consumer culture. Al-Ghazali places true happiness in the spiritual dimension through self-control, balance between needs and desires, and closeness to God. Therefore, the integration of spiritual values into economic activities becomes important to achieve a more holistic, sustainable, and relevant welfare in the face of modern societal challenges.